Memorable tourism experiences and critical outcomes among nature-based visitors: a fuzzy-set qualitative comparative analysis approach - Akhshik, Arash; Rezapouraghdam, Hamed; Ozturen, Ali; Ramkissoon, Haywantee (Routledge Journals, Taylor & Francis Ltd, 2023)
Intense global competition for natural resources, manifesting in negative environmental externalities, has forced hospitality and tourism stakeholders to adopt strategies that may result in economic growth in tandem with environmental conservation. One such strategy is to cultivate travellers' loyalty to the tourism destinations and encourage them to participate in environmentally friendly activities. Using the affective theory of social exchange, social identity, stimulus-organism-response, tourism consumption system and attachment theories, this study proposes and tests a configurational model that predicts the antecedents of visitors' pro-environmental behavioural intentions (PEBIs) regarding their desire to revisit (REVI) and recommend (RECI) the services that they experienced. Fuzzy-set qualitative comparative analysis was applied to assess the effect of memorable tourism experiences, place attachment, and demographics on these outcomes. The findings revealed that multiple configurations can predict visitors' intentions at tourist destinations. This study's implications for theory, practice, and future research directions are also discussed.
Keywords: Pro-environmental behaviour intention; revisit intention; recommendation intention; memorable experiences; place attachment